2018
DOI: 10.1016/j.eats.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Shoulder Stabilization Using a Single Portal Technique With Suture Lasso

Abstract: Open Bankart repair was the standard technique used in the past, but the request for less invasiveness, always pursued by every surgeon, pushed the development of the arthroscopic procedure. Nowadays the stabilization of the anteroinferior labrum is usually performed with an arthroscopic technique that uses the classic posterior portal and 2 anterior working portals. Because arthroscopy is progressing steadily under every aspect, there is now the chance to use only one working portal with the aid of a suture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…However, recurrence rates after arthroscopic repair have recently decreased to 5.3% in recent years. 9 Recent report shows that no differences are found between two surgical methods in other postoperative complications. 10 , 11 Besides, it is reported that the incidence of scapulohumeral periarthritis is lower after arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 98%
“…However, recurrence rates after arthroscopic repair have recently decreased to 5.3% in recent years. 9 Recent report shows that no differences are found between two surgical methods in other postoperative complications. 10 , 11 Besides, it is reported that the incidence of scapulohumeral periarthritis is lower after arthroscopic surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The most technically challenging part of arthroscopic bankart repair with the anterior single portal is to properly and perfectly position the anterior portal to reach the lowest part of the torn labrum (11). In some studies, the use of transscapular portals has been suggested to have a better view for the lower part of the lesion during arthroscopic anterior stabilization, but risks such as proximity to the axillary artery and nerve, musculocutaneous nerve and cephalic vein should be in mind (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our study, the anterior single portal was placed just above the subscapularis muscle. With this portal placement, the lowest anchor can be placed as close to the 5 o'clock position as possible and stabilization of the glenoid labrum can be achieved (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also can be associated with lower patient morbidity. 3,[8][9][10] In sports medicine, we continue to try to provide improved outcomes by decreasing size and number of incisions, and in this technique we describe a single-incision anterior labrum repair without the need for a posterior incision. Our technique uses the NanoScope (Arthrex, Naples, FL) to eliminate the posterior portal, achieving a single-incision arthroscopic anterior labrum repair.…”
mentioning
confidence: 99%